2018
DOI: 10.1021/acs.est.7b06096
|View full text |Cite
|
Sign up to set email alerts
|

Brönsted Catalyzed Hydrolysis of Microcystin-LR by Siderite

Abstract: Six naturally occurring minerals were employed to catalyze the hydrolysis of microcystin-LR (MC-LR) in water. After preliminary screening experiments, siderite stood out among these minerals due to its higher activity and selectivity. In comparison with kaolinite, which is known to act as a Lewis acid catalyst, siderite was found to act primarily as a Brönsted acid catalyst in the hydrolysis of MC-LR. More interestingly, we found that the presence of humic acid significantly inhibited catalytic efficiency of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The mineral-surface-mediated hydrolysis of pollutants generally depends on the types of acidic sites on minerals, which include Brønsted acid, Lewis acid and H-bonding sites (Figure a–c). ,,, As shown in Figure , pure CAP exhibited three distinct IR absorption peaks at 1684, 1518, and 1344 cm –1 , respectively. According to our previous study, the peak at 1684 cm –1 was attributed to the stretching vibration of the carbonyl group ν­(CO) and the conjugated CN group (Table S1), and the other two IR signals corresponded to the characteristic bands of nitryl as asymmetric ν­(ONO) and symmetric ν­(C–NO 2 ) stretching vibrations, respectively. , When CAP interacted with the Brønsted acid sites (Figure a), the carbonyl oxygen of CAP would be protonated; subsequently, the ν­(CO) band should theoretically blue-shift (∼8 cm –1 ) due to the disintegration of NCO conjugation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mineral-surface-mediated hydrolysis of pollutants generally depends on the types of acidic sites on minerals, which include Brønsted acid, Lewis acid and H-bonding sites (Figure a–c). ,,, As shown in Figure , pure CAP exhibited three distinct IR absorption peaks at 1684, 1518, and 1344 cm –1 , respectively. According to our previous study, the peak at 1684 cm –1 was attributed to the stretching vibration of the carbonyl group ν­(CO) and the conjugated CN group (Table S1), and the other two IR signals corresponded to the characteristic bands of nitryl as asymmetric ν­(ONO) and symmetric ν­(C–NO 2 ) stretching vibrations, respectively. , When CAP interacted with the Brønsted acid sites (Figure a), the carbonyl oxygen of CAP would be protonated; subsequently, the ν­(CO) band should theoretically blue-shift (∼8 cm –1 ) due to the disintegration of NCO conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that iron minerals could mediate the transformation of organic pollutants and had been used as catalysts for soil remediation. Specifically, the catalytic efficiency of iron minerals for the hydrolysis of contaminants is typically dependent on their surface properties. For example, it was reported that iron minerals, such as goethite (α-FeOOH) and hematite/maghemite (α-Fe 2 O 3 /γ-Fe 2 O 3 ), could catalyze the hydrolysis of phenyl picolinate and organophosphate via a surface chelation mechanism. Nevertheless, Mäkie et al , proposed that the surface hydroxyl groups of goethite would be responsible for the hydrolysis of organophosphates. In addition, a recent study showed that siderite (FeCO 3 ) could selectively hydrolyze microcystin-LR via a Brønsted acid catalytic mechanism .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the degradation system in the presence and absence of pyrite, the rate constants were 0.8842 and 0.0071 h −1 , and the half-lives were 0.78 and 98 h, respectively. Consequently, the presence of pyrite reduced the half-life of CYN in water by 99%, similar to the degradation systems of microcystin-LR (MC-LR) by kaolinite and siderite [12].…”
Section: Degradation Of Cynmentioning
confidence: 65%
“…The direct ethanol fuel cell (DEFC) is a new type of environmentally friendly energy conversion device and has received a lot of attention in today’s energy crisis and environmental pollution problems. The anode catalyst is an important part of the DEFC system. Pd-based catalysts have drawn more attention than Pt-based catalysts in anode catalyst research because of the lower cost and comparable activity to Pt toward ethanol electrooxidation under the alkaline system. , However, Pd-based catalysts have poor stability because they are easy to oxidize or dissolve, and this causes unnecessary loss of activity during the ethanol electrooxidation process.…”
Section: Introductionmentioning
confidence: 99%